Explosion of heterogeneous water droplet in a high-temperature gaseous region; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Piskunov M. V. Maksim Vladimirovich (Energy Efficiency and Automation Systems for Oil and Gas Facilities, 2015)
Title screen